Structural analysis of adsorption processes of 5FU and imiquimodon hydrogels using AMBER/PM3 hybrid model (2018)
AMBER/PM3 hybrid model allowed determining the structural properties of 5FU and imiquimod individually and after the adsorption of chitosan hydrogels crosslinked with genipin, respectively. It was observed that the Gibbs free energy (ΔG) decreases with the adsorption, but indicates thermodynamic stability and spontaneity in both processes; ΔG was verified by the increase in the dipole moments. On the one hand, the partition coefficient established the hydrophilic character with respect to the water present in the hydrogel, which increases with the adsorption. The FTIR showed that there were displacements in the signals, however, the hydrogen bond bands attributed to the formation of new bonds to perform the adsorption of the drugs were observed. The adsorption was verified by the MESP and the surface analysis, where the distribution of nucleophilic and electrophilic zone was observed.